School space and landscape transformation: an experience developed in remote format in a public school in São Bento / PB - Medeiros Pereira, Elaine Cristina de; Meira Garcia, Tânia Cristina (Revista Ensino de Geografia (Recife), 2021)
The changes brought about by COVID-19, triggered the instant adaptation of the daily experience of theschool space. For this reason, schools and teachers had to seek to introduce in their routine, new didactic / pedagogical strategies that came with the purpose of meeting this reality that involves the temporary suspension of face-to-face classes. In this sense, the proposed investigation deals with the experiences and reflections acquired by the execution of a didactic proposal, planned for remote teaching and anchored in the didactic / pedagogical aspects of the hybrid model, based on the curricular content ofthe Geography discipline for the 3rd year of Elementary School, Early Years. therefore, organizing a didactic activity with these aspects, allowed the student autonomy in relation to his learning process and contributed to the reflection of the teacher in relation to his practice and the importance of holding on to a flexible didactic planning, having as objective, the individual progress of each student.